Practicing Urban Citizenship in Contemporary Italy. Policies, Practices and Spaces for Same-Sex Parent Families - Monaco, Salvatore (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
In contemporary society, the national and supranational dimensions are often insufficient to describe the complexity of the citizenship’s processes. In this scenario, the city plays an active role as a political space capable of legitimizing unprecedented models of urban citizenship. Based on the main results of an empirical Italian research and using a micro-sociological perspective, the paper aims to identify four models of urban citizenship experienced by same-sex parents families. In fact, Italian same-sex parents and their children live a condition of partial citizenship at the national level, which is partially counterbalanced by a new urban morphology in which peculiar participatory practices, constructions of a sense of belonging and levels of access to rights and responsibilities take shape.